Weight Loss Activity of Boesenbergia rotunda, Zingiber cassumunar, and Hibiscus sabdariffa Combination Extract on Zebrafish Model - Indriyanti, Niken (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Boesenbergia rotunda, Zingiber cassumunar, and Hibiscus sabdariffa are potential medicinal plants to be developed as weight loss agent. This research aimed to determine weight loss activity of the 3 plants in combination. The model used was zebrafish wild type. The protocol was approved by the Ethics Committee of Health Research, Faculty of Pharmacy, Mulawarman University. The extraction method was decocta. The flavonoid and phenolic contents were calculated using standard method of analysis in Indonesian Herbal Pharmacopoeia.  The results of rendemen and total flavonoid/phenolic content (TFC/TPC) calculations are Boesenbergia extract 2,7% with the TFC of 49,7 mg/g; Zingiber cassumunar extract 6,5% with the TPC of 41,2 mg/g; Hibiscus extract 31,6% with the TFC of 91,2 mg/g. It forms as dry extracts, brown colour, and hygroscopic. The average of weight loss of zebrafish in 2 weeks treatment is 9-16% in sample 1 group; 28,5% in sample 2 group; and no lowering body weight on sample 3 group. The sample 1 and 2 are promising compared to orlistat activity, 32% weight loss. In conclusion, the highest weight loss activity is in sample 2 which is consisted of combination of Boesenbergia extract and Zingiber cassumunar extract.@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536859905 -1073732485 9 0 511 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri",sans-serif; mso-fareast-font-family:Calibri; mso-bidi-font-family:Arial; mso-ansi-language:EN-US;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-fareast-font-family:Calibri; mso-hansi-font-family:Calibri; mso-bidi-font-family:Arial; mso-ansi-language:EN-US;}div.WordSection1 {page:WordSection1;}